2013
DOI: 10.12659/msm.889349
|View full text |Cite
|
Sign up to set email alerts
|

Substance P and intensity of pruritus in hemodialysis and peritoneal dialysis patients

Abstract: BackgroundUremic pruritus is a common complication in patients undergoing dialysis. The pathophysiological mechanisms of pruritus in patients with end-stage renal disease remain unknown. Neuropeptides, including substance P, are postulated to play an important role in the pathogenesis of pruritus. The aim of this study was to evaluate the role of substance P in uremic pruritus in patients on hemodialysis and peritoneal dialysis.Material/MethodsWe included 197 patients with end-stage renal disease: 54 on contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
0
5
1
Order By: Relevance
“…Dialysis duration is an important factor affecting the prevalence of CKD-associated pruritus. Our findings indicated that the dialysis duration was negatively associated with the prevalence of CKD-associated pruritus, which was different from previous reports [11,17,35,43,45,50–54] that revealed no correlation between the 2. The following reasons could explain this phenomenon.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Dialysis duration is an important factor affecting the prevalence of CKD-associated pruritus. Our findings indicated that the dialysis duration was negatively associated with the prevalence of CKD-associated pruritus, which was different from previous reports [11,17,35,43,45,50–54] that revealed no correlation between the 2. The following reasons could explain this phenomenon.…”
Section: Discussioncontrasting
confidence: 99%
“…This meta-analysis showed that the pooled prevalence of CKD-associated pruritus in HD and PD was 55% and 56%, respectively. While some previous studies [11,63,67] had shown similar results, Min et al [10] found that HD patients had a higher prevalence of CKD-associated pruritus than PD patients. Moreover, Wu et al [9] found that HD patients had a significantly higher severity of CKD-associated pruritus than PD patients, while Mistik et al [68] showed the opposite results.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…However, few studies have directly compared the characteristics of uremic pruritus between patients with PD and HD, and their results are controversial. 15 20 Some studies reported similar prevalence of uremic pruritus among patients receiving PD and HD, 16 20 whereas other study found differences in favor of PD. 15 Furthermore, the current standard for dialysis adequacy of solute clearance has not been considered in these studies.…”
Section: Introductionmentioning
confidence: 99%